2008
DOI: 10.7213/reb.v30i70/72.22806
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade E Perfil De Resistência a Antibióticos De Coliformes Isolados De Saladas Comercializadas Em Restaurantes Self-Service

Abstract: A salada é um dos alimentos mais consumidos em restaurantes “self service”, entretanto, pode atuar como um importante veículo de transmissão de bactérias do grupo dos coliformes. Neste trabalho, foi realizada a quantificação de coliformes totais e termotolerantes presentes em saladas cruas e cozidas comercializadas em restaurantes do tipo “self-service” da cidade do Rio de Janeiro. Dentre as 37 amostras analisadas, 32 (83,8%) apresentaram contagens de coliformes termotolerantes superiores ao máximo permitido p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Hafnia alvei appeared 5 times in this study and can be found in human and animal feces, as well as in water, soil, and diverse products of animal origin [43] playing a role in the spoilage of refrigerated meat and vegetables [44]. Moreover, H. alvei can be resistant to penicillin, ampicillin, cephalothin, tetracycline, and amoxicillin/clavulanic acid [45,46] which can represent a threat from the clinical perspective.…”
Section: The Occurrence Of Coliforms At 45mentioning
confidence: 99%
“…Hafnia alvei appeared 5 times in this study and can be found in human and animal feces, as well as in water, soil, and diverse products of animal origin [43] playing a role in the spoilage of refrigerated meat and vegetables [44]. Moreover, H. alvei can be resistant to penicillin, ampicillin, cephalothin, tetracycline, and amoxicillin/clavulanic acid [45,46] which can represent a threat from the clinical perspective.…”
Section: The Occurrence Of Coliforms At 45mentioning
confidence: 99%